Arecoline hydrobromide enhances jejunum smooth muscle contractility via voltage-dependent potassium channels in W/Wv mice - Chen, Q; Jiang, Z; Zhang, J; Cao, L; Chen, Z (Physiological research, 2021)
Gastrointestinal motility was disturbed in W/Wv, which were lacking of interstitial cells of Cajal (ICC). In this study, we have investigated the role of arecoline hydrobromide (AH) on smooth muscle motility in the jejunum of W/Wv and wild-type (WT) mice. The jejunum tension was recorded by an isometric force transducer. Intracellular recording was used to identify whether AH affects slow wave and resting membrane potential (RMP) in vitro. The whole-cell patch clamp technique was used to explore the effects of AH on voltage-dependent potassium channels for jejunum smooth muscle cells. AH enhanced W/Wv and WT jejunum contractility in a dose-dependent manner. Atropine and nicardipine completely blocked the excitatory effect of AH in both W/Wv and WT. TEA did not reduce the effect of AH in WT, but was sufficient to block the excitatory effect of AH in W/Wv. AH significantly depolarized the RMP of jejunum cells in W/Wv and WT. After pretreatment with TEA, the RMP of jejunum cells indicated depolarization in W/Wv and WT, but subsequently perfused AH had no additional effect on RMP. AH inhibited the voltage-dependent K+ currents of acutely isolated mouse jejunum smooth muscle cells. Our study demonstrate that AH enhances the contraction activity of jejunum smooth muscle, an effect which is mediated by voltage-dependent potassium channels that acts to enhance the excitability of jejunum smooth muscle cells in mice.
Keywords: jejunum; nikardipin; Potassium Channels, Voltage-Gated; gastrointestinální motilita; draslíkové kanály řízené napětím; arekolin; Nicardipine; Arecoline; Dose-Response Relationship, Drug; Muscle Contraction; hladké svalstvo; blokátory draslíkových kanálů; vztah mezi dávkou a účinkem léčiva; Patch-Clamp Techniques; Gastrointestinal Motility; Mice; atropin; Animals; metoda terčíkového zámku; svalová kontrakce; Jejunum; Muscle, Smooth; myši; Atropine; Potassium Channel Blockers; zvířata